Amplification of resistance genes in Haemophilus influenzae plasmids. - Spies, T (1983)
Intramolecular amplification produces tandem repeats of tetracycline and combined tetracycline-chloramphenicol resistance determinants in conjugative plasmids of Haemophilus influenzae. This process depends on host recombination pathways. Physical mapping revealed the tetracycline transposon involved in amplification to be almost identical with Tn10, including two IS10 insertion elements. The chloramphenicol resistance determinant of the combined transposon is 1.9 kilobases (kb) in size and is bound by two 1.3-kb inverted repeats. Insertion in the close vicinity of the inside end of the left-hand IS10 generates a deletion of a 1.6-kb Tn10 region. The amplifiable units were resolved to comprise not only the respective resistance transposons, but also an additional 1.6-kb sequence (designated AS) which was demonstrated to be identically present in the different amplification systems studied. AS separates amplified transposons from each other, thereby maintaining the same orientation. Moreover, AS is present at the left flank of the transposons, but is missing at the right one. It was shown that AS represents a general constituent of the H. influenzae plasmids of the 45-kb class. Evaluation of the results suggests that AS is responsible for the recombinational events involved in the gene amplification process.